2019
DOI: 10.1097/md.0000000000015355
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide epidemiologic study for pediatric osteomyelitis and septic arthritis in South Korea

Abstract: Epidemiologic studies of pediatric bone and joint infection have been done mostly by developed Western countries, and such results could be expected to be biased. Therefore, an epidemiologic study to identify the distinct features of an Eastern country would be beneficial to improve their health outcomes and to reduce health care cost. A study was planned to investigate the epidemiology of pediatric osteomyelitis and septic arthritis in South Korea and to find out epidemiologic factors related with the occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 43 publications
(47 reference statements)
1
9
0
1
Order By: Relevance
“…The AIR of paediatric SA in WA falls within the reported incidence range from 4 to 12 per 100,000 [ 10 , 25 27 ]. While a study from Norway reported an AIR of 5 per 100,000 based on 12 cases over a 1-year period, a recent long-term study based on the Kids’ Inpatients Database (KID) in the USA reported a stable AIR of 5.5 over two decades, which is in agreement with the AIR of 5.6 in non-Indigenous patients in WA.…”
Section: Discussionmentioning
confidence: 51%
“…The AIR of paediatric SA in WA falls within the reported incidence range from 4 to 12 per 100,000 [ 10 , 25 27 ]. While a study from Norway reported an AIR of 5 per 100,000 based on 12 cases over a 1-year period, a recent long-term study based on the Kids’ Inpatients Database (KID) in the USA reported a stable AIR of 5.5 over two decades, which is in agreement with the AIR of 5.6 in non-Indigenous patients in WA.…”
Section: Discussionmentioning
confidence: 51%
“…Незважаючи на досягнення в галузі діагностики та лікування, інфекції кісток і суглобів є основною причиною захворюваності та фінансового тягаря у світі. Дослідження у Франції показало, що медичні витрати на лікування кістковосуглобової інфекції в дітей становили 5200 євро (5900 доларів США) за лікарняний день (у середньому 8,4 лікарняного дня) [21]. Гематогенний остеомієліт може бути причиною різних ступенів інвалідності.…”
Section: обговоренняunclassified
“…In Spain, when comparing 1985–1991 to 2007–2011, the incidence of orthopedic infections increased from 2.34 to 5.78 per year per 100,000 inhabitants, respectively ( Murillo et al, 2015 ). The overall prevalence of orthopedic infections in Germany increased from 15.5 to 16.7 cases per year per 100,000 inhabitants from 2008 to 2018 ( Walter et al, 2021 ), and that in South Korea increased from 7.8 to 9.1 in 2008–2016 ( Kim et al, 2019 ). It is expected that, in the near future, the number of orthopedic implant-related infections will further increase ( Piuzzi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%